Practices, Challenges, and Impacts of Implementing the “SIASA DARA” Digital Information System in the Management of Islamic Boarding Schools - Hadrian Nur; Jasiah Jasiah; Triwid Syafarotun Najah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study examines the practices, challenges, and impacts of implementing a digital information system in educational management at an Islamic boarding school in West Kotawaringin Regency. The background of this study stems from the need for Islamic educational institutions to transform and become more adaptable to technological advancements, despite various limitations such as manual administrative systems, inadequate infrastructure, and varying levels of human resource competence. The study employs a qualitative approach with a case study design to gain in-depth understanding through observation, interviews, and documentation. The findings indicate that the implementation of the “SIASA DARA” digital information system has improved administrative efficiency, strengthened institutional communication, and enhanced the quality of learning. Furthermore, students’ engagement in digital activities has fostered skill development while cultivating responsible character in technology use. Nevertheless, challenges persist regarding infrastructure and the optimal utilization of technology by educators. Overall, the integration of digital technology in Islamic boarding schools not only supports the modernization of governance but also remains aligned with Islamic values and relevant to educational needs in the digital age